Isolation and characteristics of cellulolytic bacteria based on corn waste as a fibrous feed bioactivator - Sri Wahyuni; Yunilas .; Edhy Mirwandhono; Ma'ruf Tafsin; Iskandar Sembiring (Jurnal Peternakan Integratif, 2018)
Corn waste is an agricultural product that has the potential to be used as animal feed. The aims of this study was to isolate corn waste bacteria and look for the degradation ability of bacterial fiber of corn waste as a fibrous feed bioactivator. This study was conducted in livestock production laboratory of livestock study program in faculty of agriculture, university of north Sumatra, period March to June 2018. This study used corn waste (corncob, corn straw, corn clobot, corn stalks, and corn root). Research methods used pour plate isolate methods. Parameters observed are macroscopic morphology (colony form, colony color, the edge of the colony , and colony elevesi), microscopic morphology (cell shape and gram coloring), and test the ability to degrade fiber in bacteria.  The isolation result obtained 8 isolates with varied shapes and there are 6 isolates that have ability to degrade fibers in bacteria include B2, B3, B4, B5, B6, B7. The conclusion of this study were obtained 8 cellulolytic bacteria isolates and B3 has a high potential to degrade the fiber.